2022-RA-1357-ESGO Factors associated with an increased risk of recurrence in endometrial cancer patients: a retrospective cohort study. (20th October 2022) - Teixeira, Natalia; Farres, Alba; Espanol, Pia; Magret, Eva; Luna, Rocio; Soler, Cristina; Martin-Malpartida, Pau; Macías, Maria Jesús; Céspedes, Maria Virtudes; Rovira, Ramon
Abstract : Introduction/Background: The aim of this study was to identify clinical and pathologic factors associated with the risk of recurrence in patients with endometrial cancer (EC). Methodology: We included patients who underwent surgery for EC in our institution between 2007 and 2019. Data on demographic characteristics, surgery and pathology reports, adjuvant treatment and follow-up was collected from electronic patient files. Patients were divided into two groups: recurrence and no recurrence. Clinical and pathologic factors were compared using Student T-test, Chi-square or Fisher's exact test. Univariate and multivariate Cox-proportional hazard models were used to assess the impact of the evaluated factors on the risk of recurrence. Results: In total 286 patients were included in the analysis. In a mean follow-up time of 59 months, EC recurrence was diagnosed in 60 (20.9%) patients, 75% of which were diagnosed in the first 24 months after surgery. Compared to patients with no recurrence, patients with recurrent EC had more frequently type II (56.7%vs.25.2%), high-grade (61.7%vs.32.7%), stage III-IV tumors (35%vs.17.3%), tumor>2 cm (95%vs.78.8%), myometrial infiltration>50% (48.3%vs.29.2%) and lympho-vascular space invasion (LVSI; 60.9%vs.25.8%). Lymphadenectomy had been indicated more often in patients with recurrent EC (71.7%vs.44.2%), however, there was no association between performance of lymphadenectomy and EC recurrence. In univariate survival analysis, risk of recurrence was higher in patients with type II (HR:4.12; p<0.001 ), high-grade tumors (HR:3.06; p<0.001 ), tumor>2 cm (HR:4.93; p=0.007 ), myometrial infiltration>50% (HR:2.43; p=0.001 ), cervix infiltration (HR:2.29; p<0.001 ), adnexal tumor (HR:1.97; p=0.031 ), LVSI (HR:4.39, p=0.001 ) and stage IV (HR:6.85; p<0.001 ). In multivariate analysis, only LVSI remained significantly associated with an increased risk of recurrence (HR:5.36; p=0.017 ). Conclusion: LVSI is an independent risk factor for EC recurrence, while performing lymphadenectomy had no impact on the risk of recurrence. Identifying patients with a higher risk of EC recurrence is important in order to concentrate follow-up efforts on patients who can benefit the most from it.